A STATISTICAL COMPARISON IN SELECTION OF WIRE-EDM PROCESS PARAMETERS FOR MACHINING TITANIUM ALLOY - Izamshah, Raja; Akmal, Mohd; Akmal, Mohd; Kasim, Mohd Shahir; Kasim, Mohd Shahir; Sundi, Syahrul Azwan; Sundi, Syahrul Azwan; Hadzley, Mohd; Hadzley, Mohd (Journal of Advanced Manufacturing Technology (JAMT), 2016)
Wire- EDM is one of the non-traditional processes which known as a solution for machining difficult-to-machine material. In this study, the existing parameters provided by wire-EDM machine (Mitsubishi RA90) is tested and compared for machining Ti-6Al-4V focuses on surface roughness, kerf width and material removal rate (MRR). The descriptive statistic summarizes, First Condition (HP) that uses by Mitsubishi RA90 produces higher surface roughness, kerf width and MRR compared to the other conditions. Additionally, one way ANOVA indicates there are significantly differences on surface roughness results for every conditions and only Second Condition(HP/MP) indicates all means for kerf width are equal.